New Record of Three Nematode Species of Genus Enoplus (Nematoda: Enoplidae) from Korea - Lee H.J., Rho H.S.; Jung J. (Korean J. Environ. Biol., 2015)
Three unrecorded species of free-living marine nematodes, belonging to genus Enoplus Dujardin, 1845 collected from rocky intertidal seagrass on the eastern coast of Korea, are described and illustrated. Enoplus taipingensis Zhang and Zhou, 2012 is characterized by longer body size, a series of lateral setae throughout the tail in male, the presence of trumpet-shaped precloacal supplement with well-dilated proximal end, and the presence of spicules with five to eight semicircular plates. Enoplus meridionalis Steiner, 1921 is characterized by the presence of trumpet-shaped precloacal supplement with slightly dilated proximal end, paired massive spicules, and tail with two pairs of stout terminal setae. Enoplus mammillatus Timm, 1959 is easily distinguished from the congeners by narrow tubular-shaped precloacal supplement. In this study, we provide detailed morphological features of three Enoplus species by differential interference contrast microscopy and scanning electron microscopy. This is the first report on the species of the genus Enoplus from the Korean waters.